The vital centre, the middle of nowhere, or something in-between: A study of political centrism in Western democracies - Hatem, D (2021)
The nature of the centre is one of the most significant concepts in the study of comparative politics, due to its place at the fulcrum of the ideological spectrum. However, scholarly interest in the subject has not matched its importance, with a relative paucity of research leaving the idea of the centre often poorly defined, imprecise, and theoretically muddled.